Asymmetric Curvature Side-Polished Optical Fiber Coupler - Takui Uematsu; Kazutaka Noto; Hiroyuki Iida; Chisato Fukai; Ikutaro Ogushi (IEEE Photonics Journal)
An optical fiber coupler composed of two side-polished fibers with different curvature is proposed. The live-fiber is polished with a typical radius of curvature of 0.25 m, while the branch-fiber is polished with a larger radius of curvature. Analysis shows that the proposed asymmetric structure improves the highest cross-transmission of the coupled light by up to 0.26 just by increasing the curvature of the branch-fiber (compared to the conventional symmetric arrangement) without increasing the insertion loss created by side-polishing. Experiments confirm that the proposed structure raises the highest cross-transmission by 0.15 on average when the curvature of the branch-fiber is set to 0.5 m while the curvature of the live-fiber is kept to the typical value as expected from the analysis. Our study will contribute to realizing a simple and compact machine for polishing live-fibers that offers the improved workability and portability needed for adding optical fiber couplers to live-fibers in the field.